Virtual Reality Body Exposure Therapy for Anorexia Nervosa. A Case Report With Follow-Up Results - Porras-Garcia, Bruno; Serrano-Troncoso, Eduardo; Carulla-Roig, Marta; Soto-Usera, Pau; Ferrer-Garcia, Marta; Figueras-Puigderrajols, Natàlia; Yilmaz, Lena; Onur Sen, Yigit; Shojaeian, Nazila; Gutiérrez-Maldonado, José (Frontiers in Psychology, 2020)
Objective: Exposure-based therapies such as mirror exposure may help to improve the results of classic cognitive behavioral therapy in anorexia nervosa (AN). Virtual reality (VR)-based procedures provide interesting novelties for targeting body-related concerns. This study aimed to provide preliminary evidence of the usefulness of a VR body exposure therapy in a patient diagnosed with AN. Method: Fear of gaining weight (FGW), body anxiety, drive for thinness, body image disturbances, body mass index and body-related attentional bias were assessed before and after the intervention, as well as five months later. Five sessions of VR body exposure therapy were included within the standard course of cognitive behavioral therapy. The sessions involved a systematic and hierarchical exposure of the patient to a virtual representation of her own silhouette, with the body mass index of the avatar progressively increasing in subsequent sessions. Results: After the intervention, there was a clear reduction in AN symptoms such as the FGW, drive for thinness, body-related anxiety and dissatisfaction. Body mass index values rose continuously during the intervention and reached healthy levels. Finally, there was a notable change in the dysfunctional body-related attentional bias. Almost all these improvements were maintained after five months, except for the FGW. Conclusion: To the best of our knowledge, this study is the first to focus on treating the FGW and body-related concerns in AN using a VR-based paradigm. To pursue this study further and assess the effectiveness of this new VR software, larger controlled clinical trials are needed.